Relationship-Oriented Cultures, Corruption, and International Marketing Success - Chandler, Jennifer D. (Journal of business ethics, 2010)
This study explores the general problems associated with marketing across international markets and focuses specifically on the role of corruption in deterring international marketing success. The authors do this by introducing a broader conceptualization of corruption. The dimensions of corruption and their importance in explaining the exporters’ successes in international markets are developed empirically. Partial Least Squares formative indicators are used in a comprehensive model including consumer resources (wealth and information resources), physical distance (kilometers and time zones), and cultural distance (linguistic and values differences) as alternative explanatory variables. Finally, differences in the model’s performance across data from three exporting countries (France, Japan, and the US) are delineated and discussed. For example, the successes of French and Japanese exporters in international markets are in part determined by the levels of corruption in target countries. Alternatively, corruption in target countries does not appear to affect the successes of American exporters in global markets. The conceptualization of corruption in this study extends the more narrow view of corruption solely as bribery.